2020
DOI: 10.1590/s1980-220x2019005003622
|View full text |Cite
|
Sign up to set email alerts
|

Cargas de trabalho na Estratégia Saúde da Família: interfaces com o desgaste dos profissionais de enfermagem

Abstract: RESUMO Objetivo Identificar as cargas de trabalho de equipes de enfermagem que atuam na Estratégia Saúde da Família nas cinco regiões do Brasil e as interfaces com o desgaste desses profissionais. Método Estudo qualitativo com profissionais de enfermagem de 20 Unidades de Saúde da Família, de oito munícipios das cinco regiões do país. Os dados foram coletados por meio de entrevistas e observação, sendo analisados segundo preceitos da análise temática e do referencial teórico de cargas de trabalho. Resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
4
0
5
Order By: Relevance
“…The reality of Brazilian nursing has been no different, and several studies (3,9,(17)(18)(19) were already inadequate before the pandemic, one can imagine what it has been like to work on the front line of the largest global health crisis of the 21st century, dichotomizing the idealization of heroic performance seen by society with the reality experienced by nurses in their daily work and presented in this study. Moreover, the pandemic has demanded quick actions from health professionals, such as decision making for the reorganization of health services and adaptation to the norms recommended by the scientific community for the care of suspected or infected patients (18) .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The reality of Brazilian nursing has been no different, and several studies (3,9,(17)(18)(19) were already inadequate before the pandemic, one can imagine what it has been like to work on the front line of the largest global health crisis of the 21st century, dichotomizing the idealization of heroic performance seen by society with the reality experienced by nurses in their daily work and presented in this study. Moreover, the pandemic has demanded quick actions from health professionals, such as decision making for the reorganization of health services and adaptation to the norms recommended by the scientific community for the care of suspected or infected patients (18) .…”
Section: Discussionmentioning
confidence: 92%
“…The speeches denying the title of angels and heroes can be understood as invitations to unite and articulate the category with the various sectors of civil society in search of mobilizations that combat the precariousness of health work not only during the pandemic (3) . For this, the eyes of society and managers need to be directed to the nursing workforce, providing work means, both structural and managerial, that enable a more resolute and less stressful assistance (17) . Thus, the speeches of nurses reverberate the struggle for the recognition of professional work, by means of regulations such as a workload limit for the execution of the workday and the national wage floor.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that working with an incomplete team can impair patient safety due to work overload ( 18 ) . A national study conducted with PHC nurses from several Brazilian regions identified that the professionals in Family Health teams are exposed to physical and mental workloads resulting from excessive demands and insufficient professionals, which can compromise their health and care quality ( 32 ) . A study in England highlights the relationship between increased workload and exposure to stress among health professionals involved in clinical practice and management ( 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that understanding the activities performed at work, as well as appropriate work environments, can improve the quality of patient care and reduce the professionals’ workload, increasing team and patient satisfaction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%